Microbial Load and Antibiotic Resistance of Escherichia coli and Staphylococcus aureus Isolated from Ready-to-Eat (RTE) Khebab Sold on a University Campus and Its Environs in Ghana - Azumah Ayamah; Augustina Angelina Sylverken; Linda Aurelia Ofori (Journal of Food Quality)
The demand for ready-to-eat (RTE) foods is handy to busy urban dwellers. Handling, processing, and selling are known to contaminate these foods and cause foodborne outbreaks. This study assessed a load of S. aureus and E. coli in khebabs (beef, chevon, and gizzard) sold on the KNUST campus and its environs and how resistant they are to clinically relevant antimicrobial agents. Thirty-six (36) khebab samples were purchased from vendors at Kotei, Ayeduase, Kentinkrono, Boadi, KNUST campus, and Ayigya. They were analyzed for S. aureus and E. coli and their resistance to clinically relevant antimicrobial agents checked using standard methods. S. aureus and E. coli load ranged from 4.09 to 5.96 CFU/g and 1.79 to 6.12 MPN/g in beef, 4.02 to 6.01 CFU/g and 1.99 to 4.44 MPN/g in chevon, and 5.37 to 6.18 CFU/g and 1.79 to 6.10 MPN/g in gizzard khebabs in the different locations. E. coli (n = 27) were multiresistant to ampicillin, tetracycline, gentamicin, cefuroxime, ceftriaxone, cefotaxime, and cotrimoxazole (51.85%) and susceptible to chloramphenicol (100%). S. aureus (n = 36) isolates were multiresistant to penicillin, tetracycline, flucloxacillin, cefuroxime, ampicillin (97.22%), erythromycin (75%), cotrimoxazole (86.11%), and gentamicin (69.44%). It can therefore be concluded that the majority of khebabs from the KNUST campus and its environs were contaminated with S. aureus and E. coli above the acceptable standard limits (≤4 log10 CFU/g and ˂2 log10MPN/g, respectively). Also, the S. aureus and E. coli isolated were multiresistant to the antibiotics tested and could be a medium for the transmission of antibiotic-resistant bacteria and therefore expose consumers to a high risk of contracting foodborne infections with drug-resistant strains.